Phase 1 study of C-CAR088, a novel humanized anti-BCMA CAR T-cell therapy in relapsed/refractory multiple myeloma - Yan Zhang; Lu Zhang; Xian Zhang; Xin Yao; Tingyu Wang; Dan Zhu; Liping Lan; Peihua Lu; Yihong Yao; Lugui Qiu; Xiaoyan Qu; Gang An; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Anti-B-cell maturation antigen (BCMA) chimeric antigen receptor T-cell (CAR T) therapy showed remarkable efficacy in patients with relapsed or refractory multiple myeloma (RRMM). This phase 1 dose-escalation and expansion study developed C-CAR088, a novel second-generation humanized anti-BCMA CAR T-cell therapy, and assessed the safety and efficacy of three dosages of C-CAR088 in patients with RRMM.Methods Patients received lymphodepletion with three doses of cyclophosphamide (300 mg/m2) and three doses of fludarabine (30 mg/m2) on days –5, –4, and –3, followed by an infusion of C-CAR088 on day 0. Doses of 1.0×106, 3.0×106, and 6.0×106 CAR T cells/kg (±20%) were tested in the dose-escalation cohorts and expansion cohorts. The primary endpoint was treatment safety, including the rate of treatment-emergent adverse events after cell infusion. Secondary endpoints were the overall response rate and progression-free survival. The exploratory endpoints were the quantification of C-CAR088 CAR T cells, selection of cytokines and chemokines in blood, and measurement of tumor BCMA expression.Results As of July 2, 2021, 31 patients had been infused with C-CAR088. Any grade cytokine release syndrome (CRS) occurred in 29 patients (93.5%), and grade 3 CRS occurred in 3 patients (9.7%). One patient from the high-dose group (4.5–6.0×106 CAR T cells/kg) developed grade 1 neurotoxicity. No dose-limiting toxicities were observed in any dose group, and all adverse events were reversible after proper management. The overall response, stringent complete response, complete response (CR), and very good partial response rates were 96.4%, 46.4%, 10.7%, and 32.1%, respectively. The CR rate in the medium-dose (3.0×106 CAR T cells/kg) and high-dose (4.5–6.0×106 CAR T cells/kg) groups was 54.5% and 71.4%, respectively. In the CR group, 15 (93.7%) patients achieved minimal residual disease (MRD) negativity (test sensitivity >1/10−5). All seven patients with double-hit or triple-hit multiple myeloma achieved MRD-negative CR.Conclusions The present study demonstrated that C-CAR088 had a good safety profile and high antitumor activity in patients with RRMM, constituting a promising treatment option for RRMM.Trial registration number NCT03815383, NCT03751293, NCT04295018, and NCT04322292.